Analysis of 4G LTE Internet Network Quality for Telkomsel, IM3, and 3 Providers in Prabumulih City - PALDO MALDES KANIEVPE; TIMUR DALI PURWANTO (Jurnal Jaringan Komputer dan Keamanan, 2024)
Indonesia is one of the countries with a high level of dependence on cellular communication systems. Along with rapid technological advancement, cellular networks in Indonesia continue to develop intensively, resulting in increasingly competitive service provision. The 4G Long Term Evolution (LTE) network is currently the most widely used mobile technology due to its superior data transmission speed and capacity, with download speeds reaching up to 300 Mbps and upload speeds up to 75 Mbps under optimal conditions. This study aims to analyze and compare the Quality of Service (QoS) of 4G LTE networks provided by Telkomsel, IM3, and 3 (Three) in Prabumulih City, Indonesia. The analysis was conducted using the OpenSignal, Google Maps, and Wireshark applications. OpenSignal was employed to identify the locations of Base Transceiver Station (BTS) towers, Google Maps was used to determine the distance between users and BTS locations, and Wireshark was utilized to measure QoS parameters, namely throughput, packet loss, delay, and jitter. The research adopted an action research approach consisting of planning, implementation, and evaluation stages based on QoS analysis. The results indicate significant variations in QoS among the three providers. These differences are primarily influenced by signal attenuation due to variations in user distance from BTS towers and by network congestion caused by high user density in specific locations.